Upstream. B2+: workbook - Evans V. Virginia (Newbury, Express Publishing, 2020)
Upstream B2+ is a modular secondary-level course for learners of the English language at upper-intermediate level. The series combines active English learning with a variety of lively topics presented in themed units.